Varying demands for cognitive control reveals shared neural processes supporting semantic and episodic memory retrieval - Deniz Vatansever (Nature Portfolio, 2021)
Making sense of the world around us often requires flexible access to information from both semantic and episodic memory systems. Here, the authors show that controlled retrieval from functionally distinct long-term memory stores is supported by shared neural processes in the human brain.